(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The article presents data on the effect of the use of Stop Bek, 33% and Zelek Bek 10.8% herbicides against annual and perennial weeds in cotton fields under the conditions of typical gray soils of the Tashkent region.